New circumscription and segregation of Gloxinia major (Gesneriaceae, Gesnerieae, Gloxiniinae) an endemic species from Bolivia - Lizarazu, Mabel A.; Zanotti, Christian A. (Phytotaxa, 2020)
The genus Gloxinia (Gesneriaceae, Gesnerieae, Gloxiniinae) comprises four species distributed from Nicaragua to Argentina. Historically, Koellikeria major has been problematic to place taxonomically due to the morphological similarity with Gloxinia erinoides, and as a result is currently treated as a synonym. Here, we present a molecular phylogenetic and morphological study that allowed us to demonstrate that Koellikeria major is distinct from G. erinoides. As a result, we formally transfer Koellikeria major to Gloxinia major. Here G. major is described, illustrated, and compared to morphologically similar species. Data on its distribution, habitat, and taxonomic treatment are provided.